Dixie and the Best Day Ever - Gilman, Grace; Rogers, Jacqueline 1958- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
Emma needs to write a poem for a school assignment, but she would rather go outside with Dixie and enjoy a snowy day.
Ages 4-8.
Guided reading level J.
Accelerated Reader AR
Keywords: Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Poetry -- Juvenile fiction; Snow -- Juvenile fiction; Schools -- Juvenile fiction